Pilot Study: Moving Towards a Scalable Intervention for Postgraduate Communication Skills Training - Warren Lewin; Helen James; Nikolina Mizdrak; Ben Kaasa; Shira A. Strauss; J. Thomas Toguri (Palliative Medicine Reports)
Background: Communication skills are foundational to the practice of medicine and training to build them is recommended. Serious illness communication skills (SICSs) teaching is inconsistently and sparsely taught in postgraduate training and residents report feeling inadequately trained to have difficult conversations. The authors developed an e-module demonstrating high-yield communication skills from a known evidence-based training program to standardize core SICS teaching and questioned how using it before skills practice impacted comfort and preparedness for residents to complete advance care planning (ACP). Methods: Family medicine residents at an academic hospital in Toronto, Canada, completed a novel e-module that replaced a typical didactic-lecture introducing core SICS relevant to ACP conversations. Residents then discussed the skills, followed by practicing them deliberately in a structured role-play simulation with feedback by trained facilitators. Residents completed pre- and post-intervention attitudinal surveys. Results: Residents preferred a combination of learning modalities and welcomed online and virtual teaching methods for learning SICS. Residents reported higher levels of preparedness for engaging in ACP, delivering serious news, and discussing goals of care post-intervention. Residents showed more interest in discussing ACP post-intervention but questioned feasibility for doing so in busy ambulatory clinics. Conclusion: Scalable time-efficient teaching strategies are needed to fill a known education gap. This study demonstrated benefits of incorporating brief e-module learning into residents’ preparation for SICS training using deliberate practice simulation training. The online, interactive virtual training improved resident readiness and comfort for ACP, an area often overlooked in medical education. Moreover, it provides an evidence-informed standardized tool for clinician teachers to seamlessly incorporate into their teaching practices.